Kernels of derivations of polynomial rings and Casimir elements - Bedratyuk, L. P.; Бедратюк, Л. П. (Institute of Mathematics, NAS of Ukraine, 2010)
We propose an algorithm for the evaluation of elements of the kernel of an arbitrary derivation of a polynomial ring. The algorithm is based on an analog of the well-known Casimir element of a finite-dimensional Lie algebra. By using this algorithm, we compute the kernels of Weitzenböck derivation $d(x_i ) = x_{i−1},\; d(x_0) = 0,\;i = 0,…, n$, for the cases where $n ≤ 6$.